Is Water an Input to a Fish? Problems with the Production-Function Model in Education - Hodas, Steven (Education Policy Analysis Archives, 1993)
The concept of a production-function as a metaphor of the educational process is critiqued. In particular, Monk's (1992) discussion of the production-function is seen as typical of the final stages of a dying paradigm.